Higher Education Marketing Strategy: Comparative Study of State Islamic Universities and State Universities - Fadhli, Muhammad; Salabi, Agus Salim; Siregar, Fauzan Ahmad; Lubis, Harun; Sahudra, Tengku Muhammad (Jurnal Ilmiah Peuradeun, 2023)
The increasing of State Islamic Universities (PTKIN) in Aceh is contradictory with the minimum interest of Acehnese to study at PTKIN. This phenomenon shows an anomaly in Acehnese religiosity level. This paper aimed to seek Higher Education (HE) marketing strategies in Aceh and to describe the reason for Acehnese low interest in PTKIN. A mixed method was used in this research; meanwhile, an explanatory sequential design was chosen to be the research design. This research was done in 3 PTKIN and 3 State Universities (PTU) in Aceh, where 60 Acehnese students were chosen as respondents. Besides quantitative data, qualitative research was done by interviewing, observing, and studying documentation to get more information. The result showed that the products (departments and accreditation) significantly affected students' interest in HE. This article suggested that PTKIN add more departments to present many choices for society as a place to study at a high education level.